Analisa Perkembangan Dan Kearifan Tempatan: Karya Fiqh Melayu Klasik: Analysis of Development and Local Wisdom Classical Malay Fiqh Works - Malik, Mohd Puaad Abdul; Abdul Hamid, Faisal @ Ahmad Faisal; Abd Rahim, Rahimin Affandi (Jurnal Fiqh, 2020)
This article focusses on the subject of classical Malay fiqh works which are intellectual works of Malay Muslim scholars in various Islamic legal topics whether ‘ibadat, mu‘amalat, munakahat and others. These works play important roles in the Malay community as a means of communication, knowledge, and scientific development. This article analyzes the historical development of classical Malay fiqh works to present the concept of local wisdom based on Islamic Malay literature. The method of analysis used is historiography that examines the development of an idea. Facts obtained will be thoroughly screened using the Malay induction history approach. Discussion from the intellectual aspect shows that Malay fiqh works are the result of the Malay Muslim local wisdom. Those works are unique in their identity as a means of understanding and developing knowledge in the Malay world. They also brought a dynamic change to intellectual development in the Malay world and in conformity with the teachings and practice of Islam. They are also not stereotype in nature but high in value and quality.